INTEGRATING SYSTEMIC FUNCTIONAL LINGUISTICS IN DESIGNING SYLLABUS FOR ELT CLASSROOM - Arfan Fahmi (Institut Teknologi Sepuluh Nopember, 2010)
To communicate effectively language learners need to become proficient in using the semantic, syntactic, lexical, morphological and phonological elements of the language being learnt. They also need to understand its pragmatics use. Accounting those requirements, the focus of ELT should have tended on grammatical, thematic, and functional approaches to syllabus design. A theory of language that is in line with this is Systemic Functional Linguistics (SFL). SFL can support the communicative language teaching in some extents. Firstly, this theory focuses on meaning and how language operates to make meaning at text level. In other words, it goes beyond traditional approaches’ learning of isolated rules of exemplified in decontextualized sentences. Another good point to take SFL in ELT is that this theory stresses how meanings are made or negotiated in actual communication with other people. It is focused on real language use in authentic situations. Thirdly, this theory is really ‘communicative’ in the extent that it explores language based on its use in context. It takes into account three factors that relate to the context in which the language is being used: FIELD (what is being talked), TENOR (who is talking, and what is the relationship between them), and MODE (mode: spoken or written). These three factors are the realization of what to do to be able to communicate well. What is also important is that it considers the social purpose of the language as well. It is mediated in the so called as GENRE. In Communicative Language Teaching (CLT), the primary objective is to provide language learners with the information practice and much of the experience needed to meet the communication needs in the second or foreign language. This article discusses the relation between SFL and CLT in the iumplementation of syllabus design for ELT classroom. It is doubtful whether anyone will ever come up with a perfect syllabus for ELT, the one that will ensure success with every kind of learner in every kind of context. It is difficult, if not impossible, to have a nationally uniformed syllabus of ELT. Learning and teaching contexts are too varied in terms of class size, resources, exposure to the target language outside the classroom, and many others. The basic principle is that the materials should be presented gradually, given in a communicative context, in an integrative, not discrete, way.